1990
DOI: 10.1007/bf00271984
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of parvalbumin-specific immunoreactivity in the cerebral cortex and hippocampus of the developing rat and gerbil brain

Abstract: Developmental changes in the distribution of parvalbumin-specific immunoreactivity in the brain, in particular in the cerebral cortex and hippocampus, were followed immunohistochemically in two different species, the rat and the Mongolian gerbil (Meriones unguiculatus) using an antibody raised against for rat parvalbumin. The gerbil is known to develop its auditory and visual capacity later than rat. In both the rat and gerbil, parvalbumin-specific immunoreactivity appeared after birth in both the cerebral cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
46
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 23 publications
5
46
0
Order By: Relevance
“…In earlier studies, we found high PV-specific immunoreactivity in the central auditory system of the rat and gerbil where it appeared in parallel with the functional maturation of the neurons (20,21). In this study, we examined the distribution of PV-like immunoreactivity in the human central auditory system , H2O and lyophilized.…”
mentioning
confidence: 87%
“…In earlier studies, we found high PV-specific immunoreactivity in the central auditory system of the rat and gerbil where it appeared in parallel with the functional maturation of the neurons (20,21). In this study, we examined the distribution of PV-like immunoreactivity in the human central auditory system , H2O and lyophilized.…”
mentioning
confidence: 87%
“…During the development of the gerbil, the dot-like staining appeared close to newly-immunoreactive cells, but was not observed in areas with no immunopositive cells, even if there was uniform scattering of punctate staining for synaptophysin (data not shown). The rat parvalbuminspecific antiserum used in our previous study (36) hardly recognized dot-like structures in these areas, but did stain densely condensed dot-like structures in the anterodorsal thalamic nucleus of the gerbil (36). Thus, the level of parvalbumin molecules in the dotlike structures of the cerebral cortex and hippocampus may be low.…”
Section: Discussionmentioning
confidence: 68%
“…The occurrence of parvalbumin immunoreactive cells has been described for the VCN in the last embryonic day of rats (Solbach and Celio, 1991). For adult rats Aoki et al (1990) found that about 30% of the neurones in DCN contain parvalbumin.…”
Section: Discussionmentioning
confidence: 97%